2021
DOI: 10.1038/s41398-020-01103-x
|View full text |Cite
|
Sign up to set email alerts
|

Default mode and salience network alterations in suicidal and non-suicidal self-injurious thoughts and behaviors in adolescents with depression

Abstract: Suicidal ideation (SI) and non-suicidal self-injury (NSSI) are two distinct yet often co-occurring risk factors for suicide deaths in adolescents. Elucidating the neurobiological patterns that specifically characterize SI and NSSI in adolescents is needed to inform the use of these markers in intervention studies and to develop brain-based treatment targets. Here, we clinically assessed 70 adolescents—49 adolescents with depression and 21 healthy controls—to determine SI and NSSI history. Twenty-eight of the d… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
36
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(41 citation statements)
references
References 73 publications
3
36
0
2
Order By: Relevance
“…Together, many of these regions also contribute to the salience and default mode networks. A recent study found that in a sample of adolescents, patients with depression and NSSI demonstrated reduced connectivity at rest within the salience and default mode networks relative to patients with depression but no NSSI and healthy controls (Ho et al, 2021). A strength of this study is the use of both clinical and healthy controls, which suggests that findings may be unique to NSSI rather than due to general psychopathology.…”
Section: Social / Self Neural Systemsmentioning
confidence: 80%
“…Together, many of these regions also contribute to the salience and default mode networks. A recent study found that in a sample of adolescents, patients with depression and NSSI demonstrated reduced connectivity at rest within the salience and default mode networks relative to patients with depression but no NSSI and healthy controls (Ho et al, 2021). A strength of this study is the use of both clinical and healthy controls, which suggests that findings may be unique to NSSI rather than due to general psychopathology.…”
Section: Social / Self Neural Systemsmentioning
confidence: 80%
“…Clinical characteristics of the included samples were diverse, with one study including only BPD patients and another only depressed individuals [ 26 , 35 ]. Psychiatric comorbidity was common among individuals who reported NSSI.…”
Section: Resultsmentioning
confidence: 99%
“…Only one study employed a network-based approach and found diminished coherence between the default mode and salience networks and higher connectivity between the central executive and default-mode networks [ 26 ]. They also reported an association between higher past-month NSSI and lower coherence in the default mode and insula salience networks [ 26 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations